Ready to be Open? Explaining the Firm Level Barriers to Benefiting From Openness to External Knowledge. Issue 2 (April 2017) - Monteiro, Felipe; Mol, Michael; Birkinshaw, Julian
Abstract : This paper provides new theory and evidence about the benefits of openness on a firm's innovation performance and, more importantly, the specific firm-level contingencies under which those benefits are more (or less) likely to be observed. Building on Dyer and Singh's (1998) relational view, we suggest that a firm's lack of resources and absorptive capacity, as well as its use of secrecy, are significant barriers to benefiting from openness to external knowledge. Using responses from 12, 152 firms to the fourth and fifth UK versions of the Community Innovation Survey (CIS), we generate findings consistent with our hypotheses.